Red-green-blue analysis of nasal mucosa discolouration in allergic rhinitis. - Toprak, A; DEĞİRMENCİ, NAZAN; Degirmenci, Nazan; Dogan, R; TUĞRUL, SELAHATTİN; Senturk, E; ŞENTÜRK, EROL; Tugrul, S; TOPRAK, ALİ; Ozturan, O; ÖZTURAN, ORHAN (My University, 2020)
Objective To evaluate the colour values of nasal mucosa for the purpose of presenting an objective parameter of allergic rhinitis. Methods Seventy-three patients with allergic rhinitis (allergy group) and 73 normal healthy individuals (control group) were included in the study. Endoscopic examinations were conducted, and endoscopic photographs of the septum and both inferior turbinates were taken. The Adobe Photoshop Elements 7.0 software program was used to measure the numerical values of red-green-blue (RGB) colour components in the endoscopic photographs of nasal mucosa. Results The G and B values were significantly higher in the allergy group compared to the control group (both p < 0.05). Cumulative R, G and B values of all measurement points were significantly higher in the allergy group compared to the control group (p < 0.05). Conclusion Nasal mucosa discolouration can be measured objectively with RGB analysis to aid the diagnosis of allergic rhinitis.